An Obstacle Avoidance Method for Action Support 7-DOF Manipulators Using Impedance Control - Masafumi Hamaguchi; Takao Taniguchi (Journal of Robotics)
An obstacle avoidance method of action support 7-DOF manipulators is proposed in this paper. The manipulators are controlled with impedance control to follow user's motions. 7-DOF manipulators are able to avoid obstacles without changing the orbit of the end-effector because they have kinematic redundancy. A joint rate vector is used to change angular velocity of an arbitrary joint with kinematic redundancy. The priority of avoidance is introduced into the proposed method, so that avoidance motions precede follow motions when obstacles are close to the manipulators. The usefulness of the proposed method is demonstrated through obstacle avoidance simulations and experiments.